AJARAN ISLAM NUSANTARA DI DALAM KAMUS SANTRI TIGA BAHASA INDONESIA-INGGRIS-ARAB KARYA SLAMET RIYADI DAN AINUL FARIHIN (STUDI ANALISIS SEMIOTIKA DAN KONSEP PRIBUMISASI ISLAM ABDURRAHMAN WAHID) - Muhammad Agus Mushodiq; Suhono Suhono (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
This research aims to find out the sign meaning of the conversations displayed in the dictionary. So that it need the interpretation of meaning holistically as a sign. Furtheromre to find out the form and the basic religiouse teaching of Islam Archipelago on three indonesia-English-Arabic Language. The researchers used Sanders Peirce Theory to analyze the signs which contained in the conversations presented by the Three Language Santri Dictionary. So that it will be found the meaning of the values ​​presented each conversation is studied. Peirce viewed the sign as a triadic structure. The three dimensions that build the structure are; Representament, object, and interpretant. Thus the researchers tried to be as detailed and demanding as possible to examine every sign of these diomension. The Researchers sort out the conversations that contain the Islamic Archipelago concept and analyze the sign intensively and gradually in each conversation so that found the general meaning or argument major. On the other hand the researchers also use the theory of Abdurrahman Wahid’s Islamic Indigenousization to analyze the values ​​of Islamic Archipelago. The result showed that this study directed at: (1) the call to implement amar ma'ruf nahi munkar lovingly and nihilisme physical and mental violence, (2) the legality of birthday celebration, especially the memorial of the Prophet's mawlid, (3) revitalization of ideology of nationalism; Love of the homeland, (4) the legality of the idea of ​​gender equality in Indonesia, and (5) the legality of hanging a photo on the wall of the house. Key Words: Charles Sandra Peirce Theory, Triadic Structure, Abdurrahman Wahid’s Islamic Indigenousization, The values ​​of Islamic Archipelago